PENGARUH TAX PLANNING, PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019 - ZENSEN ZENSEN; SOVIA LOLITA A. PARDEDE; CORINNA WONGSOSUDONO (LP2MTBM MAKARIOZ, 2022)
This study aims to examine the effect of Tax Planning, Profitability, and Liquidity on firm value in Real Estate and Property Companies listed on the Indonesia Stock Exchange for the 2015-2019 period, either partially or simultaneously. The data in this study is secondary data obtained from the Indonesia Stock Exchange website. The source of the research data is the financial statements of Real Estate and Property companies downloaded from the Indonesia Stock Exchange website from 2015 to 2019. The number of samples used are 24 companies taken from a population of 45 companies with an observed year number of 5 years so that the number of observations in the study This is a total of 120 observations. The analytical method used in this research is using multiple regression analysis, partial test, simultaneous test and determination test, where previously the classical assumption test has been carried out. The results showed that profitability and liquidity had a significant effect on firm value with a significant value less than 0.05, while tax planning had no effect. Simultaneously, tax planning, profitability and liquidity have a significant effect on firm value in Real Estate and Property Companies listed on the Indonesia Stock Exchange for the 2015-2019 period as evidenced by a significant value less than 0.05.